Predictive value of cerebral natriuretic peptide in acute myocardial infarction without obstructive coronary disease. (3rd May 2023) - Rocha Carvalho, P; Goncalves, F; Carvalho, C; Bernardo, M; Fontes, P; Moreira, J I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The brain natriuretic peptide (BNP) has a protective role on the coronary vasculature. On the other hand, vascular dysfunction is one of the main factors associated with acute myocardial infarction without obstructive coronary disease (MINOCA). Therefore, one can theorize that BNP might be involved in the pathophysiological mechanism of this disease. Purpose: This study sought to determine whether a low BNP value is a significant predictor of MINOCA. Methods: This was a national multicenter retrospective study of patients hospitalized for an acute myocardial infarction (AMI) between October 2010 and September 2019. Patients with previous history of heart failure, severe valvular disease, chronic kidney disease, atrial fibrillation and who didn't have a coronary angiography during hospitalization were excluded. Results: Of a total of 4954 patients with an AMI, 306 (6, 2%) were diagnosed as MINOCA. The MINOCA group had a higher percentage of women (42, 5% vs 24, 6%, p<0, 001) and was more frequently hospitalized for a non-ST-segment elevation myocardial infarction (70, 9% vs 39, 3%, p<0, 001). Left ventricular ejection fraction was significantly higher in these patients (58±13% vs 54±13%, p=0, 002). MINOCA was associated with a better in-hospital prognosis: less cardiogenic shock (1, 0% vs 4, 0%, p=0, 008), less cardiac arrests (1, 0% vs 4, 8%, p=0, 002), less major bleeding events (0% vs 1, 8%, p=0, 019) and lower mortality (0% vs 2, 2%, p=0, 010). The BNP median was lower in patients with MINOCA (91 (38;269) pg/mL vs 141 (56;328) pg/mL, p<0, 001). The BNP cut-off, determined by ROC curve analysis, was 85, 5pg/mL. Therefore, 49, 3% of the patients with MINOCA had BNP values considered low, in contrast to 35, 3% of the patients with obstructive coronary disease (p<0, 001). In a multivariate regression analysis, we found that a low BNP value was a significant predictor of MINOCA (adjusted OR 2, 46, 95% CI 1, 87-3, 23). Conclusions: As expected, MINOCA was an entity associated with a better in-hospital prognosis when compared to AMI with obstructive coronary disease. In this study, a low BNP value was able to independently and significantly predict MINOCA.